Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Ninjaxpress di Kabupaten Nganjuk - Dhani Khasbul Wafi; Supriyono Supriyono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This Research aims to measure customer satisfaction of Ninjaxpress in Nganjuk. It will give benefit for the merchant of Ninjaxpress Nganjuk which sell their product into Marketplace such as Lazada, Shopee and Tokopedia. The customer satisfaction will make the business environment more professional specifically in online business. By understanding, customer satisfaction of Ninjaxpress Nganjuk, the merchant will accelerate their product shipment to end customer. The methodology used is Partial Least Square (PLS) with quantitative approach. The data is collected from literature review, business report, and survey which is distributed to 65 loyal customers from Ninjaxpress in Nganjuk using purposive sampling. Purposive sampling uses inclusive criteria which are above 17 years old and they are experienced using Ninjaxpress Services. The result of this research is that Quality (X) has positive impact with customer satisfactions (Y), with path coefficients 0,876508, T-Statistic Value 23,327372 > 1,96 (From table Zα = 0,5) or P-Value 0,000 < 0,05. There is a positive coloration between the quality of services and customer satisfactions Keywords: Service Quality, customer satisfaction